Price Mechanisms in Green Electricity Markets and Game Analysis of Participant Behavior - Liu, Jing; Chen, Tiantian; Xiao, Yiqing; Wang, Jing (E3S web of conferences, 2025)
As the global demand for carbon reduction continues to grow, promoting green electricity has become a key to achieve sustainable development. However, effectively incentivizing green electricity generators and quota subjects to participate widely in green electricity trading remains a challenge. This study constructs a bipartite network model based on the game between green electricity generators and quota subjects to analyze the impact of green electricity prices, traditional electricity prices, and green certificate market prices on decision-making behavior. The results show that an increase in green electricity prices significantly enhances market participation, while an increase in traditional electricity prices reduces the proportion of green electricity participation. This study provides a theoretical basis for formulating reasonable price mechanisms and policy incentives to promote the adoption of green electricity.